Passive actuator-fault-tolerant path following control of autonomous ground electric vehicle with in-wheel motors. (August 2019) - Chen, Te; Chen, Long; Xu, Xing; Cai, Yingfeng; Jiang, Haobin; Sun, Xiaoqiang
Highlights: A novel passive actuator-fault-tolerant path following control method of autonomous ground electric vehicle with in-wheel motors is proposed by hierarchical control strategy. The proposed control method is designed to improve the vehicle lateral stability and ensure the path following accuracy simultaneously in case of the failure of vehicle actuator. The estimation methods of system states and fault are developed and an optimal tire force distribution method is designed to satisfy the control demand. Abstract: This paper investigates the fault-tolerant path following control problem of autonomous ground electric vehicles with in-wheel motors through hierarchical control strategy. The sliding mode observer with boundary layer is designed to estimate the vehicle state, and the time-delay estimation method is used to compute the actuator fault. Considering the actuator fault, the fault-tolerant path following control strategy is proposed, in which the upper layer controller is developed to achieve path following control and guarantee vehicle stability simultaneously by sliding mode control method, and the lower layer controller is presented to achieve the control efforts of upper layer controller by adaptive orientated tire force allocation method. The simulations are implemented in the CarSim-Simulink co-simulation platform, and the simulation results have verified the effectiveness of proposed fault-tolerant path following control method.